Papers - Copper and Brass - Deoxidation of Copper with Calcium and Properties of Some Copper-calcium Alloys (With Discussion) - Earle E. Schumacher; W. C. Ellis; John F. Eckel (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1930)
Copper-calcium alloys are of interest as materials for use in deoxidized conductors of high conductivity. That calcium is effective in deoxidizing and degasifying copper is well known. Brandenberg and Wiensl have described the use of calcium in the casting of sound copper and state that the deoxidation can be carried out without difficulty. The castings that they prepared were sound and sufficiently ductile to permit wire drawing. Pratt,2 in British Patent No. 1699 (1907), has claimed the use of calcium for the deoxidation and degasification of copper. Masing3